Socio-Historical and Cultural Influences on Visual Differentiation of Wayang Kulit of Cirebon, West Java, Indonesia: A Case Study of the Attributes Differentiation of Priest Drona Puppets - Koesoemadinata, Moh Isa Pramana; Sabana, Setiawan; Adisasmito, Nuning Damayanti (TAWARIKH, 2013)
ABSTRACT: The âwayang kulitâ (shadow play) is a traditional art of theatre that popular in Java and Bali, and considered as a multidimensional state of art which consists dimension of theatrical, literature, philosophy, moral education, and not to mention visual arts and crafts dimension as well, in which is the main discussion of this paper. There are several styles of Javanese âwayang kulitâ based on their geographical area. Among those, Cirebon style possesses unique visualization which has resemblance to early phase of Islamic era âwayangâ puppet. One of the character transformations done which includes personality and visual descriptions happened to the Priest Drona, the vital character of Mahabharata that role as âguruâ (teacher) to both Pandawas and Kurawas, who was trapped inside dilemma between his warring disciples. In the adaptation version of Javanese shadow play, for some various and speculative reasons, Drona has been altered into an antagonistic character, and reached its extreme point of alteration as an absolute evil character in Cirebon version. Cirebonâs history, culture, and plural society gave significant influence on this. Drona puppets themselves have unique and specific visual attributes in comparison to other main characters puppets, and possess highly symbolic meaning beneath them. These facts told us that the character has a great significance. Later, these negative connotations of Drona was being sharpened and escalated in accordance of socio-historical events and local phenomenon, thus producing visual differentiation within the Drona puppets.KEY WORDS: âWayang kulitâ, Drona character, Cirebon area, visual, differentiations, attributes, socio-historical events, and symbolic meaning.Â Â Â Â About the Authors: Moh Isa Pramana Koesoemadinata, M.Sn. is a Student of Doctoral Program at the Faculty of Visual Arts and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10, Tamansari, Bandung, West Java, Indonesia. Prof. Dr. Setiawan Sabana and Dr. Nuning Damayanti Adisasmito are Lecturers at the Faculty of Visual Arts and Design ITB. Corresponding author is: dronacarya@yahoo.co.idHow to cite this article? Koesoemadinata, Moh Isa Pramana, Setiawan Sabana & Nuning Damayanti Adisasmito. (2013). âSocio-Historical and Cultural Influences on Visual Differentiation of Wayang Kulit of Cirebon, West Java, Indonesia: A Case Study of the Attributes Differentiation of Priest Drona Puppetsâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.43-56. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 5, 2013); Revised (September 9, 2013); and Published (October 28, 2013).